The Impact of Corporate Social Responsibility on Sustainable Innovation: A Case in China’s Heavy Pollution Industry - Yan, Rui; Li, Xiaolin; Zhu, Xiaoning (Frontiers in Psychology, 2022)
Exploring the impact of corporate social responsibility (CSR) fulfillment and disclosure on enterprises’ sustainable innovation capacity can not only expand the research boundary of factors of sustainable innovation and the impact of CSR, but it can also serve as a reference for the decision-making of listed companies in increasing pollution problems. Using a sample of 224 Chinese A-share businesses in the heavy pollution industry listed between 2016 and 2020 and employing an ordinary least square regression, the results provide empirical evidence that CSR is positively associated with sustainable innovation. Second, the business environment can serve as a moderator of the relationship between CSR and sustainable innovation, and the positive relationship between CSR and sustainable innovation is more pronounced in regions with better macroeconomic conditions. Additionally, the improvement of CSR for sustainable innovation is more clear in state-owned firms than in non-state-owned enterprises. After a series of robustness tests that eliminate marketization, law enforcement, and macro-political unpredictability, the results still hold. This study broadens the scope of CSR and sustainable innovation research. In addition, the theoretical and practical significance of this study’s findings is referenced in this paper.